Analysis of Mispronunciation of MakhÄrij Al-HurÅ«f in Arabic HiwÄr Learning - Kosim, Nanang; Ali, Eldaw Awadelkarim; Ruhani, Nursakinah; Senita, Putri (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This research aims to identify the locations of mispronunciations of the makhÄrij al-hurÅ«f in conversations (hiwÄr) in the VII PPS Babussalam class in the city of Bandung. Additionally, it serves as an evaluation tool for Arabic language learning to improve the learning process and provide solutions or treatments to students to enhance their makhÄrij al-hurÅ«f pronunciation. Correcting makhÄrij al-hurÅ«f errors is crucial as they can affect the meaning. This research utilizes a qualitative descriptive research method. The population of this research includes all the students in the VII PPS Babussalam class in the city of Bandung, and it was conducted on May 17, 2023, at the VII PPS Babussalam class in Bandung. Data collection involved interviews, tests, and documentation, followed by analyzing all data in narrative form. Based on the research findings, it can be concluded that there are 426 mispronunciations of makhÄrij al-hurÅ«f in the hiwÄr in the VII PPS Babussalam class in Bandung. These errors include mispronunciations in Al-Jauf (Mouth Cavity), totaling three errors with a percentage of 0.70%, falling into the deficient category; mispronunciations in Al-halq (Throat), totaling 204 errors with a percentage of 47.89%; falling into the high category; mispronunciations in al-lisÄn (Tongue), totaling 171 errors with a percentage of 40.14%, also falling into the high category; mispronunciations in al-syafatain (Two Lips), totaling 35 errors with a percentage of 8.22%, falling into the low category; and mispronunciations in Al-Khaiysyum (Nasal Cavity), totaling 13 errors with a percentage of 3.05%, falling into the low category. These pronunciation errors occur due to the student's lack of understanding of the correct makhÄrij al-hurÅ«f pronunciation, such as not being aware of the pronunciation differences between Indonesian and Arabic, the absence of specific attention from teachers to correct each student's pronunciation, and the lack of practice. This study recommends further research in analyzing the mispronunciation of makhÄrij al-hurÅ«f letters with different research objects, namely the mispronunciation of makhÄrij al-hurÅ«f letters in Arabic news.